A Dedication ‘to the Olympian Gods’ for Hadrian’s Sōtēria: Saluting the Emperor’s Rural Passage through Syria-Palestina - Giambrone, Anthony (Palestine exploration quarterly, 2025)
An unpublished squeeze from the collection of the École biblique, recording a dedication to the ‘Olympian Gods’ for Hadrian's sōtēria, is here presented in conversation with two closely related inscriptions, recently identified as fakes. The authenticity and provenance of the new object are carefully analysed and discussed and a conclusion cautiously in favour of its genuine antiquity is proposed.